Evaluation of organophosphorus and synthetic pyrethroid insecticides against six vector mosquitoe species Avaliação de inseticidas organofosforados e piretroides sintéticos contra seis mosquitos vetores - Domingo Montada Dorta; V. Vasuki; A. Rajavel (Universidade de São Paulo, 1993)
Three organophosphorus compounds- malathion, folithion and temephos- and two synthetic pyrethroids- alphamethrin and deltamethrin- were used for monitoring the susceptibility status of larvae and adults of six vector mosquitoe species: Culex quinquefasciatus (Filariasis) and Aedes albopictus (Dengue) (both laboratory and field strains); laboratory strains of Aedes aegypti (Dengue), Anopheles slephensi and Anopheles culicifacies (Malaria), and Culex tritaeniorhynchus (Japanese encephalitis) in India. From the LC50 values obtained for these insecticides, it was found that all mosquito species including the field strains of Cx. quinquefasciatus and Ae. albopictus were highly susceptible Except for Cx. quinquefasciatus (field strain) against malathion, 100% mortality was observed at the discriminating dosages recommended by World Health Organization. The residual effect of alphamethrin, deltamethrin, malathion and folithion at 25 mg (ai)/m² on different surfaces against six species of vector mosquitoes showed that alphamethrin was the most effective on all four treated surfaces (mud, plywood, cement and thatch). Nevertheless, residual efficacy lasted longer on thatch than on the other surfaces. Therefore, synthetic pyrethroids such as alphamethrin can be effectively employed in integrated vector control operations. Três compostos organo-fosforados - malation, folition e temefos -e dois piretroides sintéticos - alfametrina e deltametrina - foram usados para controlar o estado da susceptibilidade das larvas e adultos de seis mosquitos vetores na Índia. Foram utilizadas cepas de laboratório e área de Culex quinquefasciatus (filariasis) e Aedes albopictus (Dengue) e cepas de laboratório de Aedes aegypti (Dengue), Anopheles stephensi e Anopheles culicifacies (Malária) e Culex tritaenorhynchus (encefalite japonesa). Os valores de C1(50) obtidos para esses inseticidas mostram que todas as espécies incluindo as cepas de área foram muito susceptíveis. Nos mosquitos adultos das referidas espécies salvo na cepa da área de Culex quinquefasciatus com o malathion, observou-se 100% da mortalidade às doses discriminatórias recomendadas pela Organização Mundial de Saúde. O efeito residual da alfametrina, deltametrina, malation e folition a 25 mg (ai)/m² em diversas superfícies contra seis espécies de mosquitos vetores evidenciou que a alfametrina foi a mais efetiva em todas as superfícies tratadas (argila, "plywood", cimento e palha).